Religious Court Judge’s Perception granting the Right to Livelihood in Judicial Divorce Cases Based on the Judge's Ex Officio Rights - Widya Mayang Yuninda; Ali Maskur (Fakultas Syariah Institut Agama Islam Negeri Palu, 2024)
This study discusses the wife’s nafkah right in a judicial divorce. The purpose of this study is to determine the legal considerations of the judges of the Ternate Religius Court, Bulukumba Religius Court, and Singkil Sharia Court in deciding judicial divorce cases that are considered nusyuz but the wife get nafkah iddah. This research is a library research where the collected data are cases with the legal problem regarding nafkah iddah for wife who sues her husband for divorce. The approach to this research is the statuate approach. It is an approach used by examining the Law and its regulations regarding the legal issues raised. Beside, the researcher also uses the historical approach. This approach is used by analyzing the judge's decision to decide cases that are not yet legally certain in the Law. Next, the data is processed by a a descriptive data analysis technique then the conclusions written deductively. The results in this study indicate that not always the wife who files for a judicial divorce can be considered nusyuz because in fact, the wife is the aggrieved party such as being cheated on, not given nafkah during an argument and experienced physical violence by her husband. So that in this case the judge can give the nafkah right to the wife as long as she is not proven to be nusyuz by SEMA Number 3 of 2018 which accommodates PERMA Number 3 of 2017 as a regulation that binds litigated and ex officio judges in order to achieve justice.